PENGARUH UKURAN PERUSAHAAN, TINGKAT HUTANG, KEPEMILIKAN MANAJERIAL, KOMITE AUDIT TERHADAP PERSISTENSI LABA - Aprilia Maharani Firdousy; Dirvi Surya Abbas; Daniel Rahandri; Indra Gunawan Siregar (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of this study was to determine the effect of firm size, debt level, managerial ownership, audit comitte on earnings persistence in property and real estate companies listed on Indonesia Stock Exchange (IDX). The research time period use is 6 years, namely the 2016-2021 period. The sampling technique use purposive sampling technique. Based on the predetermined criteria obtained 15 companies. The type of data use is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis. The result showed that the company’s debt level had no effect on earnings persistence. Meanwhile, cash flow volatility has a effect on eranings persistence.